Determinants of tuberculosis: an example of high tuberculosis burden in the Saharia tribe - Gupta, Parul; Singh, Pushpendra; Das, Aparup; Kumar, Ravindra (Frontiers in Public Health, 2023)
Tuberculosis (TB) is a significant public health problem among the Saharia community, an underprivileged tribal group in west-central part of India. There are several challenges for India's TB control program to curtail TB in Saharia tribe due to various factors. Malnutrition, poor health sector facilities, lower socio-economic status, substance abuse are interconnected and synergistic factors contributing to a high burden of TB in Saharia tribe. In this review, efforts are made to collate the findings of previous studies discussing the causes of high burden of TB in Saharia tribe, social gaps for mitigating these preventable risk factors of TB in Saharia tribes and the plausible solutions for closing these gaps. The concept of Health in All Policies and intersectoral co-ordination is needed for reduction of TB in Saharia tribe and making India TB-free by the year 2025.